Interactive Horror Story and the Narratives Implementation: Case Study on Interactive Story Games Developed by Supermassive Games - Pratama, Galih Dea; Junior, Franz Adeta; Handoyo, Alif Tri; Majiid, Muhammad Rizki Nur; Ardiyanto, Elshad Ryan; Purnomo, Fredy (Journal of Games, Game Art, and Gamification, 2024)
Video game is one of many media designed to provide entertainment to its targeted users. In response to that, narrative that presents story to engage the users in many ways, such as through interactive story that responds to the actions taken by the players during the gameplay. To understand how the narrative is brought in the games, there is analytical framework specifically presented to break down the elements included in the games like storyworld, character, emotion, narrative interface and micro-narrative. In this research, the analytical framework is used to analyze the interactive horror story games developed by Supermassive Games, taking deeper look on the elements brought by each game. There are various implementations on each of the games, from the storyworld resembling numerous popular horror thriller media, presence of multiple playable characters, emergence of emotions like Fear and Anxiety among others, and the existence of micro-narratives to supplement the main story.